PEMANFAATAN TUMBUHAN PANGAN PADA MASYARAKAT SEKITAR CAGAR ALAM HUTAN BAKAU PANTAI TIMUR (CAHBPT) KECAMATAN MENDAHARA KABUPATEN TANJUNG JABUNG TIMUR PROVINSI JAMBI: (Utilization Of Food Plants In The Community Around The Mangrove Forest Reserve East Coast (CAHBPT) District Mendahara District Tanjung Jabung East Jambi Province) - Nursanti Nursanti; Ade Adriadi; Afni Yunita (Fakultas Kehutanan Universitas Jambi, 2021)
Indonesia is a country that has a high biodiversity, both in the diversity of flora and fauna. Indonesia has about 40.000 biodiversity types of plants that are useful for human life. Plants are one of the biological resources that are available in nature. Plants are widely used by the public both as food medicines, rituals, cosmetic materials, animal feed and so forth. The utilization of plant species depends on the surrounding area, for example in mangrove forests. Jambi Province has a Coastal area that is located in Tanjung Jabung Barat and Tanjung Jabung Timur. Coastal communities are people who live in coastal areas that have different characteristics Coastal communities have interactions with mangrove ecosystems so that people use mangrove plants as food crops, medicines, building materials (boards), traditional ceremonies and for household appliances. This research was conducted in June-August 2020 located in Mendahara Ilir Village, Lagan Ilir Village and Sinar Kalimantan Village, Mendahara District, Tanjung Jabung Timur, Jambi Province. The method in this study is explorative Descriptive. Data collection techniques in this study consist of four stages, namely: literature studies, interviews, field observations and herbarium making. There are 14 species of plants that can be used as food ingredients in the community around East Coast Mangrove Nature Reserve.